In Situ Fabrication of Vertical Multilayered MoS2/Si Homotype Heterojunction for High‐Speed Visible–Near‐Infrared Photodetectors. Issue 8 (7th January 2016) - Zhang, Yan; Yu, Yongqiang; Mi, Longfei; Wang, Hui; Zhu, Zhifeng; Wu, Qingyun; Zhang, Yugang; Jiang, Yang
Abstract : c2D transition metal dichalcogenides (TMDCs)‐based heterostructures have been demonstrated to achieve superior light absorption and photovoltaic effects theoretically and experimentally, making them extremely attractive for realizing optoelectronic devices. In this work, a vertical multilayered n‐MoS2 /n‐silicon homotype heterojunction is fabricated, which takes advantage of multilayered MoS2 grown in situ directly on plane silicon. Electrical characterization reveals that the resultant device exhibits high sensitivity to visible–near‐infrared light with responsivity up to 11.9 A W –1 . Notably, the photodetector shows high‐speed response time of ≈30.5 µs/71.6 µs and capability to work under higher pulsed light irradiation approaching 100 kHz. The high response speed could be attributed to a good quality of the multilayer MoS2, as well as in situ device fabrication process. These findings suggest that the multilayered MoS2 /Si homotype heterojunction have great potential application in the field of visible–near‐infrared detection and might be used as elements for construction of high‐speed integrated optoelectronic sensor circuitry. Abstract : A high‐speed vertical multilayered n‐MoS2 /n‐silicon homotype heterojunction is fabricated by taking advantage of multilayered MoS2 grown in situ directly on plane silicon. The device exhibits high sensitivity to visible–near‐infrared light and a capability to follow pulsed light irradiation approaching 100 kHz.